2010
DOI: 10.1007/s00439-010-0917-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk sum score comprised of common polygenic variation is associated with body mass index

Abstract: Genome-wide association studies (GWAS) of body mass index (BMI) using large samples have yielded approximately a dozen robustly associated variants and implicated additional loci. Individually these variants have small effects and in aggregate explain a small proportion of the variance. As a result, replication attempts have limited power to achieve genome-wide significance, even with several thousand subjects. Since there is strong prior evidence for genetic influence on BMI for specific variants, alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 57 publications
3
52
2
Order By: Relevance
“…Many genomic variants together contribute to overall risk (termed polygenic risk) for a number of complex traits [Peterson et al, 2011; Hamshere et al, 2013; Meyers et al, 2013], and this genetic architecture is evident in a number of psychiatric conditions—including BP [Purcell et al, 2009; Lee et al, 2012, 2013; Smoller et al, 2013; Bramon et al, 2014]. While the elucidation of the genetic causes for BP has been challenging, the field is progressing in understanding the genetic architecture of this complex disorder (reviewed in [Craddock and Sklar, 2013]) and in identifying specific genes which increase risk [Sklar et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
“…Many genomic variants together contribute to overall risk (termed polygenic risk) for a number of complex traits [Peterson et al, 2011; Hamshere et al, 2013; Meyers et al, 2013], and this genetic architecture is evident in a number of psychiatric conditions—including BP [Purcell et al, 2009; Lee et al, 2012, 2013; Smoller et al, 2013; Bramon et al, 2014]. While the elucidation of the genetic causes for BP has been challenging, the field is progressing in understanding the genetic architecture of this complex disorder (reviewed in [Craddock and Sklar, 2013]) and in identifying specific genes which increase risk [Sklar et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al (2010) included 12 SNPs that explained 0.9 % of BMI variation in Europeans, Takeuchi et al (2011) calculated a GRS with 14 SNPs that explained 0.65 % among Japanese, and Peterson et al (2011) included 56 SNPs explained 0.66 % of the variation in BMI among a mixed sample of European-and African-Americans. We calculated a GRS in this study using 5 obesity GWAS SNPs that overlap with Li et al (2010), 7 obesity GWAS SNPs that overlap with Takeuchi et al (2011), and 9 obesity GWAS SNPs that overlap with Peterson et al (2011). Taken together, these results suggest that while considerable progress has been made in gene discovery, obesity SNPs highly replicated in GWAS do not yet predict a significant proportion of the heritability attributed to adiposity phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence comes originally from adoption and twin studies (1,2) and has been confirmed in recent genome-wide association (GWA) studies, in which a number of risk alleles for overweight / obesity have been identified (3)(4)(5)(6)(7). Combining such genetic variants in a risk score appears to be an appropriate measurement of an individual's genetic predisposition for overweight (8,9). In a previous study, we found that such a genetic risk score was associated with differential effect sizes depending on children's body composition, with greatest effects on higher body mass index (BMI) percentiles (10).…”
Section: Introductionmentioning
confidence: 98%